Israel : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
This 2002 Article IV Consultation highlights that the Israeli economy is in the midst of a deep recession. Waning exports and investment, combined with stagnant private consumption, led to negative growth in 2001 and 2002. The stagnation can be attributed to the burst of the technology bubble, the global slowdown, and the deterioration in the security situation. Recently, some indicators suggested that economic activity is stabilizing, but there are no signs of recovery in sight. On the structural front, the government has pushed forward a broad-based tax reform and introduced some labor market reform measures.